Voice from the front-line - Rose-Martland, Jeff (Henry Stewart Talks, 2009)
Simple contact center organization, Types of contact centers, Why have agents?, What are agents?, Reality, Dehumanization, Quality evaluation, Frustration, Contact center survival plan
Archived at 2025/05/28